NANOPARTICLES IN WATER PURIFICATION AND WASTE-WATER TREATMENT: A COMPREHENSIVE REVIEW - Ajai Kumar S Molakeri; Shilpa Kodge (International Educational Journal of Science and Engineering, 2026)
This review paper examines the nanoparticles based approaches for water purification and waste-water treatment and their interactions with biological systems. It discusses the applications of nanoparticles in biofouling prevention, disinfection, biomonitoring, and diagnostics. The review emphasizes on the use of nanoparticles such as TiO2, ZnO, N2O, AgO, CuO, SiO2, Al2O3, and CeO2 in waste-water treatment plants and their toxic effects on microbial communities. It also explores the applications of carbon-based nanomaterials in water and waste-water treatment, including their role in adsorption, disinfection, and membrane separation mechanisms. The advantages, limitations, research needs, and challenges of carbon-based nanomaterials are critically evaluated. It also highlights the role of nanotechnology in monitoring and treating rising hazardous wastes in water, soil, and air environments. Various nanomaterials, including antibacterial nanoparticles, carbon-based nanoparticles, and metal oxide nanoparticles, are discussed in relation to treating contaminants like greenhouse gases, organic pollutants, heavy metals, and pathogens. The paper emphasizes the need for cost-effective and stable materials and methods in the water industry to meet the growing demand for potable water. It explores how nanotechnology-based processes can provide affordable solutions without relying on large infrastructures or centralized systems. It reviews the of nanoparticles/fibers applications in removing a range of pollutants from water and waste-water and provides recommendations for implementing nanotechnology in the water industry.